A study on the development of strategic tools for study orientation skills towards achieving academic excellence in the university - Awang, Mohd Ghani; Sinnadurai, Suriya Kumar; Abdul Wahab, Muhammad Nubli (2008)
The purpose of this research is to develop study orientation strategic tools towards achieving academic excellence among first year Engineering students of University Malaysia PAHANG. The measurement of study orientation skills is done by innovating a website based on a survey of study habits and attitudes questionnaire (SSHA); http://portal.ump.edu.my/survey. The students' study orientation skilis are analyzed and sorted into three groups of achievement; the higher achiever, normal achiever and lower achiever. The strategic tools comprise of the treatment website; http://portal.ump.edu.my/surveyladmin, a textbook (Study Orientation Skills in Action, Kit (Study Orientation Skills Kit), Ghani format of note-taking, DVD on the study orientation skills and lecture on each aspects of study orientations skills. The assessment on the academic performance is based on grade point average (GP A) scores of the undergraduates in their first semester and second semester examination results. 7 4 respondents selected by simple random sample taken from the Faculty of Civil Engineering & Natural Resources. The research uses Quasi-experimental design with a pre-test and post-test by comparing both group samples. The finding has shown that the study orientation skills (SOS) website was able to measure SOS effectively among the respondents in the two groups. There is a significant difference in SOS between pre-test and post test scores of the respondents. The results also show that there is a correlation between SOS and GP A scores in pre-test and post-test within and between each group.